Peranan Praktek Menjahit di Lembaga Kursus dan Pelatihan (LKP) Inun: Strategi Pemberdayaan Perempuan - Budi Harahap, Aisyah (Fakultas Dakwah dan Ilmu Komunikasi, 2019)
Inun Institute for Training and Training (LKP) is an institution under the auspices of the Binjai City Women's Empowerment Office authorized in the field of women's empowerment through a sewing skills program. The institution aims to create skilled workers in the field of sewing clothes. The institute educates trainees totaling 20 people consisting of housewives and women dropping out of school under experienced instructors. This training runs for 3 months. It is expected that after receiving training, participants will be able to be independent and be able to open their own jobs. This study aims to determine the role of LKP Inun in empowering women through sewing skills programs, as well as the economic impact after receiving training. The research method used is in the form of a qualitative study with literature. Data obtained from interviews, non-participant observation, and documentation.The results of the study found that trainees succeeded in increasing family income. It was evident from interviews that trainees could help with their children's education costs from the results of sewing wages.Lembaga Kursus dan Pelatihan (LKP) Inun merupakan lembaga dibawah naungan Dinas Pemberdayaan Perempuan kota Binjai yang berwenang dibidang pemberdayaan perempuan melalui program keterampilan menjahit Lembaga yang bertujuan menciptakan tenaga terampil dibidang penjahitan pakaian ini memberdayakan perempuan khususnya di kota Binjai agar mampu mandiri dalam bidang perekonomian. Lembaga tersebut mendidik peserta latihan yang berjumlah 20 orang yang terdiri dari ibu rumah tangga dan wanita putus sekolah di bawah instruktur yang berpengalaman. Pelatihan ini berjalan selama 3 bulan. Diharapkan setelah mendapatkan pelatihan, peserta mampu mandiri dan bisa membuka lapangan pekerjaan sendiri. Penelitian ini bertujuan untuk mengetahui peran LKP Inun dalam memberdayakan perempuan melalui program keterampilan menjahit, serta dampak perekonomian setelah mendapatkan pelatihan. Metode penelitian yang dipakai berbentuk kualitatif dengan pendalaman pustaka. Data didapat dari wawancara, observasi non partisipan, serta dokumentasi. Hasil dari penelitian didapat bahwa peserta latihan berhasil meningkatkan pendapatan keluarga. Terbukti dari wawancara bahwa peserta latihan bisa membantu biaya pendidikan anaknya dari hasil upah menjahit.Kata Kunci: Pemberdayaan, Perempuan